1997
DOI: 10.1097/00001756-199705260-00029
|View full text |Cite
|
Sign up to set email alerts
|

Visual motion activates V5 in dyslexics

Abstract: A recent functional magnetic resonance imaging (fMRI) study concluded that the motion-specific visual area V5 is not activated in dyslexic subjects. We report here opposing evidence based on whole-scalp neuromagnetic recordings. Apparent-motion stimuli elicited similar activation of V5 in both dyslexic and control subjects, with a trend for longer latencies in dyslexics. Both high- and low-contrast stimuli activated the V5 region in dyslexics. The lack of significant blood flow changes despite modified neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 11 publications
6
31
0
2
Order By: Relevance
“…This area has been shown to be active in monkeys almost immediately after V1 (2) and suggested to be active even before V1 in humans (33). However, the 170-to 220-ms latencies in our study are in line with earlier magnetoencephalographic data showing V5 activation at 160 ms for motion stimuli (32,34). It is possible that our stimuli did not activate V5͞MT, but the signals with longer latencies at the ROI c come from other functional areas.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This area has been shown to be active in monkeys almost immediately after V1 (2) and suggested to be active even before V1 in humans (33). However, the 170-to 220-ms latencies in our study are in line with earlier magnetoencephalographic data showing V5 activation at 160 ms for motion stimuli (32,34). It is possible that our stimuli did not activate V5͞MT, but the signals with longer latencies at the ROI c come from other functional areas.…”
Section: Resultssupporting
confidence: 87%
“…The temporo-occipital source region was about 1 cm anterior and inferior to human MT͞V5 (x, y, and z Talairach coordinates for the ROI c are 42, Ϫ67, and Ϫ4 mm, respectively; data have been compared with a summary of V5 coordinates in ref. 32). However, because of its size, the ROI c should include activation of the human V5͞MT.…”
Section: Resultsmentioning
confidence: 99%
“…The average Talairach and Tournoux (1988) coordinates of our LOV5 source (Vanni et al, 2004) are very close to the coordinates of V5 reported in earlier studies (Eden et al, 1996;Tootell et al, 1995;Vanni et al, 1997;Watson et al, 1993). Also, in monkeys, this region is known to react to onset of a stimulus as well as to visual motion (Felleman and Kaas, 1984;Schmolesky et al, 1998).…”
Section: Discussionsupporting
confidence: 87%
“…Some of these physiological and psychophysical findings have not been replicated (Victor et al, 1993;Walther-Muller, 1995;Hayduk et al, 1996;Johannes et al, 1996;Vanni et al, 1997). Consequently, the hypothesis for an M pathway deficit in dyslexia remains controversial.…”
Section: Abstract: Mt; V1; Neuroimaging; Fmri; Speed Discrimination;mentioning
confidence: 99%
“…First, visual evoked potentials (VEP) in dyslexics were reduced or delayed for stimuli with low spatial and high temporal frequencies (Livingstone et al, 1991;May et al, 1991;Lehmkuhle et al, 1993;Kubova et al, 1996). Second, in a functional magnetic resonance imaging (fMRI) study, Eden et al (1996) failed to find significant activity in MTϩ during the perception of moving dots in dyslexic subjects, suggesting a possible developmental lesion in MTϩ.Some of these physiological and psychophysical findings have not been replicated (Victor et al, 1993;Walther-Muller, 1995;Hayduk et al, 1996;Johannes et al, 1996;Vanni et al, 1997). Consequently, the hypothesis for an M pathway deficit in dyslexia remains controversial.…”
mentioning
confidence: 99%